Antibiotic Use Among Residents Receiving Skilled Nursing Care in 29 U.S. Nursing Homes. Issue 2 (9th October 2020) - Song, Sunah; Wilson, Brigid M.; Bej, Taissa; Gravenstein, Stefan; Carter, Rebecca R.; Marek, Joseph; Jump, Robin L. P.
Abstract : BACKGROUND: Data describing antibiotic use in U.S. nursing homes remain limited. We report antibiotic use among skilled nursing facility residents from 29 U.S. nursing homes and assessed correlations between antibiotics prescribed to residents in skilled care and nursing home characteristics. DESIGN: Retrospective cohort study. SETTING: Twenty‐nine U.S. nursing homes in the same healthcare corporation. PARTICIPANTS: Residents receiving skilled care in 2016. MEASUREMENTS: We used pharmacy invoice and nursing home census data to calculate the days of antibiotic therapy per 1, 000 days of skilled care (1, 000 DOSC), the rate of antibiotic starts per 1, 000 DOSC, the length of antibiotic therapy, and the average antibiotic spectrum index. We also assessed correlations between antibiotic use and nursing home characteristics. RESULTS: Antibiotics accounted for an average of 9.6% (±0.6%) of systemic medications prescribed among residents receiving skilled care. On average, 26.8% (±2.9%) of antibiotics were intravenous. Fluoroquinolones were prescribed at the highest rates (19% across all facilities), followed by beta‐lactam/beta‐lactamase inhibitors (11%), first‐ and second‐generation cephalosporins, sulfonamides, and oral tetracyclines (each at 9%). Both the proportion of residents using enrolled in Medicare and number of unique prescribers responsible for systemic prescriptions positively correlated with the rate of antibiotic starts. CONCLUSIONS: Our study demonstrates that pharmacy invoices represent a useful and preexisting source of data for assessing antibiotic prescriptions among individuals receiving skilled nursing care. The correlation between the number of unique prescribers and antibiotic starts suggests that prescribers are central to efforts to improve antibiotic use in nursing homes.